Computers, privacy and data protection an element of choice - Gutwirth, Serge; Poullet, Yves; De Hert, Paul; Leenes, Ronald (Springer, 2011)
Privacy and data protection have never been static. On the contrary, the history of the last 40 years shows the reverse. New issues and challenges continue to emerge, requiring an ongoing process of interpreting their effect in terms of reach, objectives and their deeper significance. Indeed, the consequences of technological applications due to unprecedented storage, processing and transmission capacities and to the possibilities of miniaturization, convergence, interoperability and ubiquity, represent powerful triggers and challenges to emerging developments, but they are certainly not the only determining factor. The current developments are also linked to many other sources of action and change, such as business models, security policies, population management, police work and law enforcement, leisure, culture, health policies, practices in the real and in the virtual world and so on. In the face of such dynamism, the "element of choice unambiguously evokes both the need to collectively take responsibility and direct those developments in a desirable direction, providing the ambit to influence and steer the course of things in a way that matches our expectations not only toward privacy and data protection, but also more broadly, to the kind of world we are building. This challenge is not an easy one since all big policy choices we might be willing to make are conditioned by a myriad of small decisions and bifurcations that have already set many small switches in irreversible positions. In one way or another, all the contributions to this book express the complexity of making choices regarding issues of privacy and data protection. This is all the more relevant given that the 1995 EC Data Protection Directive, the centerpiece of European data protection, is being revised as these sentences are written